Kegiatan Ekstrakurikuler Pramuka Dalam Membentuk Sikap Kepemimpinan Melalui Kecerdasan Emosional Peserta Didik - Dewi, Kumala Vera; Fachradilla, Winda (STIE Bina Karya, 2024)
Scouting extracurricular activities have an important role in shaping leadership attitudes through the development of students' emotional intelligence. This study aims to determine the effect of Scouting extracurricular activities in shaping leadership attitudes through emotional intelligence. This type of research is descriptive research with a quantitative approach. The data used in this study are quantitative data obtained from primary data with a questionnaire data collection technique given to research respondents. The population of this study were students of SMA Negeri 1 Sei Suka who participated in extracurricular activities at the school while the sample used were students who participated in scouting extracurricular activities, which were 56 people. The data processing technique used in this study was PLS (Partial Least Square) with the help of SmartPLS software. The results of the study showed that scouting extracurricular activities had a positive and significant effect on leadership attitudes, scouting extracurricular activities had a positive and significant effect on emotional intelligence, emotional intelligence had a positive and significant effect on leadership attitudes, and scouting extracurricular activities had a positive and significant effect on leadership attitudes through emotional intelligence.